Better Students Ask More Questions.
f(x) = 4*x^3 + 2* e^2x is invertible :: Find d/dx (f^-1(2))
1 Answer | add yours
We know by defnition of inverse function.
Let `g=f^(-1)` ,then
differentiating (i) with respect to x ,implicitly
one of the solution of (iv) is x=0
so substitute x=0 in (iii) ,we have `f'(0)=4`
Thus from (ii)
Posted by pramodpandey on May 1, 2013 at 9:22 AM (Answer #1)
Related QuestionsSee all »
Join to answer this question
Join a community of thousands of dedicated teachers and students.